2021
DOI: 10.1186/s12912-021-00534-1
|View full text |Cite
|
Sign up to set email alerts
|

Social justice in health system; a neglected component of academic nursing education: a qualitative study

Abstract: Background In recent decades, increasing social and health inequalities all over the world has highlighted the importance of social justice as a core nursing value. Therefore, proper education of nursing students is necessary for preparing them to comply with social justice in health systems. This study is aimed to identify the main factors for teaching the concept of social justice in the nursing curriculum. Method This is a qualitative study, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…As some authors recommend, as future health care professionals, they will have to promote critical thinking to identify social injustices in their communities (e.g., inequities on ethnic minorities) as they will have to protect them (Cuellar, 2021). Furthermore, insisting on and providing further education on the importance of empowering nurses in policy decision-making (e.g., proposing feasible and holistic actions recognizing and involving the role of different stakeholders) should be a responsibility for nurse educators (Habibzadeh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As some authors recommend, as future health care professionals, they will have to promote critical thinking to identify social injustices in their communities (e.g., inequities on ethnic minorities) as they will have to protect them (Cuellar, 2021). Furthermore, insisting on and providing further education on the importance of empowering nurses in policy decision-making (e.g., proposing feasible and holistic actions recognizing and involving the role of different stakeholders) should be a responsibility for nurse educators (Habibzadeh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Education in social determinants of health, social justice, and sociocultural competence should be an essential element integrated throughout the degree programs. These points are insufficiently taught in nursing programs (Alemany-Arrebola et al, 2021;Demirtas et al, 2021;Habibzadeh et al, 2021). Moreover, no research has been found in which students reflected about how the virus influences those at a higher risk of suffering its wider consequences (specifically in ethnic minorities and socioeconomically vulnerable groups).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nursing students' fatalistic explanations for poverty could explain why they tended to underscore the economic burden that people living in poverty caused rather than affirming the responsibility that policymakers had to end poverty. Moreover, it could be argued that the concept of social justice is insufficiently taught in undergraduate nursing education (Habibzadeh et al, 2021). The inclusion of the social determinants of health in accreditation standards for nursing programs should be considered, as Mahoney et al (2020) emphasised in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse and midwifery educators also need to critically review their responsibilities and approaches for developing capacity of graduates in addressing key social justice issues and providing culturally responsive approaches to perinatal mental healthcare. Habibzadeh et al (2021) reports on the lack of attention paid to social justice in nursing and midwifery curriculum. Incorporating learning opportunities that explore cultural responsiveness of perinatal mental healthcare is one approach to integrating social justice principles into everyday learning and teaching strategies.…”
Section: Introductionmentioning
confidence: 99%